Implementation of Project-Based Learning to Enhance Students’ Writing Achievement in Higher Vocational Education - Gusti Nyoman Ayu Sukerti; Kadek Yogi Susana (Politeknik Negeri Bali, 2018)
The educational policy in higher vocational education particularly aims at accommodating the workplace requirements both in the area of practical and soft skills. Self-management, collaborative skill and problem solving are among sought-after soft skills needed to be acquired by the students. Project-based learning provides the incorporation of those skills as it involves series of phases which require students to perform self-directed or autonomous learning. This article presents results of the study concerning the impact of project-based learning implementation to students’ writing achievement. Participants were 64 second semester students from three different classes enrolled in a three-year undergraduate program in Informatics Management. Students were involved in series of project-based learning phases until the final products, i.e., essay with multiple effects and infographic were uploaded into students’ social media account. This classroom action research applied quantitative design and the data including pre-test and post-test scores were analyzed using SPSS statistic 21. Paired-sample t-test was used to analyze whether or not there was a significant difference in students’ English writing achievement before and after being taught using PBL. The study revealed that students gained higher mean score in their second essay and there was a strong impact of PBL in improving students’ achievement in writing. Considering the positive result of this study, PBL is recommended to be applied in teaching English for students in higher vocational education as it gives beneficial impact on students’ content learning and soft skills.